2017
DOI: 10.1038/srep46258
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of expression of the circadian clock gene Period causes metabolic abnormalities including repression of glycometabolism in Bombyx mori cells

Abstract: Abnormalities in the circadian clock system are known to affect the body’s metabolic functions, though the molecular mechanisms responsible remain uncertain. In this study, we achieved continuous knockdown of B. mori Period (BmPer) gene expression in the B. mori ovary cell line (BmN), and generated a Per-KD B. mori model with developmental disorders including small individual cells and slow growth. We conducted cell metabolomics assays by gas chromatography/liquid chromatography-mass spectrometry and showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 81 publications
(90 reference statements)
0
28
0
Order By: Relevance
“…GC-MS is suitable for the analysis of small-molecule, thermostable, volatile, gasifiable compounds, while LC-MS can analyze compounds with higher polarity, higher relative molecular mass, and poor thermal stability. Numerous studies have shown how these techniques may be used to complement each other 34 36 . Zhou et al .…”
Section: Discussionmentioning
confidence: 99%
“…GC-MS is suitable for the analysis of small-molecule, thermostable, volatile, gasifiable compounds, while LC-MS can analyze compounds with higher polarity, higher relative molecular mass, and poor thermal stability. Numerous studies have shown how these techniques may be used to complement each other 34 36 . Zhou et al .…”
Section: Discussionmentioning
confidence: 99%
“…CCGs are involved in various physiological activities, including cell proliferation, apoptosis, cell cycling, metabolism, endocrine signaling and immunity (4)(5)(6)(7)(8). As a result, abnormal expression of clock genes can lead to a variety of diseases, including endocrine disorders, cardiovascular diseases and tumors (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is now clear that changes in gene expression levels also can determine phenotypic outcomes ( e.g. , Bakar et al 2015 ; Rose et al 2016 ; Schweizer et al 2016 ; Lotan et al 2017 ; Tao et al 2017 ). Because of this, connections between genetic polymorphisms and changes in expression levels revealed by eQTL mapping provide powerful insights into the mechanistic pathways underlying the genotype–phenotype relationship ( e.g.…”
mentioning
confidence: 99%